Long-term field experiments carried out in savannas and hillsides agroecosystems by Soil Biology (PE-2: Soils project of CIAT) - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
The soil biology (PE-2: Soils project of CIAT) had several field experiments in both tropical savannas and hillsides agroecosystems. The data collected from 1990 to 2000 were organized systematically.